(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Atazanavir is a human immunodeficiency virus (HIV) protease inhibitor. Due to its intense lipophilicity, the oral delivery of atazanavir encounters several problems such as poor aqueous solubility, pH-dependent dissolution and rapid first-pass metabolism in liver by CYP3A5, which result in low and erratic bioavailability. The current study aimed to develop self-nanoemulsifying drug delivery systems (SNEDDS) of atazanavir in an attempt to circumvent such obstacles. Equilibrium solubility studies indicated the choice of peceol oil - acrysol EL135-capmul MCMC8 for formulating the SNEDDS. Ternary phase diagram constructed with surfactant (Acrysol EL135), co-surfactant (Capmul MCMC8) and oil (peceol oil) representing each apex of the triangle. The pharmacokinetics studies of SNEDDS formulation were investigated in wistar rats. The optimal formulation (F9) with best self-nanoemulsified and solubilization ability consisted of 20% (w/w) peceol oilas oil, 60% (w/w) acrysol EL135 as surfactant and 20% (w/w) capmul MCMC8 as cosurfactant. The formulation displayed maximum drug content of 99, 98% entrapment efficiency and drug release of >98% in 60 minutes. The particle size for the optimized formulation of SNEDDS (F9) was found to be 51.6 nm with PDI 0.468 and zeta potential of -20.6 mV. The formulation found to be stable after storage at accelerated conditions at 40 ± 2°C/75 ± 5% RH for a period of six months. The pharmacokinetic study in rats indicate that the Cmax of the SNEDDS 0.33 ± 1.73 ng/mL was significant (p < 0.05) as compared to the pure drug 0.091 ± 0.39 ng/mL. Tmax of both SNEDDS formulation and pure drug was 1.5 ± 0.53 and 3 ± 0.72 hours, respectively. The AUC indicated significant enhancement in the rate and extent of bioavailability by the SNEDDS formulation compared to pure drug. The studies, therefore, indicate the successful formulation development of SNEDDS with distinctly improved bioavailability of atazanavir.